Trace metal concentrations in sediments from the southwest of the Iberian Peninsula - Julián Blasco (Scientia Marina, 2010)
Metal sediment concentrations (As, Cd, Cu, Hg, Ni, Pb and Zn) in surface sediments (0 to 5 cm) from 11 sampling stations in the southwest of the Iberian Peninsula (the Ria Formosa and the Guadiana River, the Ría de Huelva and the Bay of Cadiz) were determined in two seasonal periods (autumn 2006 and spring 2007). No seasonal metal concentration pattern was identified, as similar values were found in both periods. The highest concentrations of copper, zinc, lead and cadmium were reported in the Ria of Huelva area, and those of mercury and nickel in the Bay of Cadiz. The hazard potential index (HPiM) was determined to assess the potential risk associated with metal contamination (Cu, Cd, Pb and Zn), taking into account extractable (presumed bioavailable) fractions of these metals and site-specific sediment quality values. When the HPiM is > 1 there is risk, and according to this index Ría de Huelva is polluted whereas the Bay of Cadiz is not.